Nursing mattress framework and medical nursing mattress with sit-up and turn-over functions - CAI GUIPING (2020)
The invention discloses a nursing mattress framework and a medical nursing mattress with sit-up and turn-over functions. The nursing mattress framework comprises two sets of longitudinally-arranged turning-over assemblies. Another at least one group of transversely-arranged turnover assemblies are further arranged between the two groups of longitudinally-arranged turnover assemblies; the turning-over assembly comprises a deformable framework and a driving assembly, and the deformable framework is a long-strip-shaped chain which is composed of a plurality of chain links located on the same straight line and extends in the horizontal direction. The driving assembly can move back and forth along the deformable framework and can drive any two adjacent chain links in the deformable framework torotate relatively. By arranging the turnover assembly with the chain-shaped deformable framework, the deformable framework can be controlled to be turned over at any adjacent chain link according tothe position condition of